Improving Absolute Earthquake Location in West Texas Using Probabilistic, Proxy Ground‐Truth Station Corrections. Issue 11 (7th November 2019) - Lomax, Anthony; Savvaidis, Alexandros
Abstract: An increase in induced seismicity in the central United States since 2009 led to establishment of TexNet seismic‐monitoring in Texas. Accurate, absolute seismic‐event location is critical to TexNet, allowing quantitative evaluation of possible association of seismicity with human activity. For the Delaware Basin, western Texas, relocation using different velocity models and TexNet station subsets shows absolute location error up to 4–5 km. The preferred method to reduce absolute error, ground‐truth calibration, is not available in this area. Alternatively, we used industrial well activity as proxy, ground‐truth for developing probabilistic, proxy ground‐truth (PPGT) station corrections for relocation. Assuming well activity causes seismicity, we defined a distance–time probability associating events and well activity. We used these associations and other evidence to show some seismicity in the Delaware Basin is more likely due to hydraulic‐fracturing than saltwater disposal. We then probabilistically accumulated PPGT station corrections using event hypocenters constrained to associated fracturing‐well locations. We applied this procedure within 12 km of TexNet station PB02, optimizing the procedure through comparison of rates of causal and acausal associations. Relative to the initial locations, final PPGT relocations show smaller residuals and shifts in epicenter as much as 3 km, predominantly toward the north and northwest. PPGT residuals are similar to those from relocation with standard station corrections. The initial hypocenters showed an unreasonable deepening with distance from station PB02, whereas PPGT relocations produced an overall flattening of event depths. These results are consistent with PPGT corrections giving real improvement in absolute location accuracy. Plain Language Summary: The TexNet seismic‐monitoring program in Texas was established in response to an increase in human‐induced earthquakes in the central United States since 2009. Accurate determination of the geographic location and depth in the Earth of earthquakes is critical to TexNet monitoring, allowing potential association of earthquakes with human activity. But accurately locating earthquakes is difficult due to lack of geologic knowledge and sparsity of seismic monitoring stations. For a study area in western Texas, errors in TexNet earthquake location and depth may be as much as 4–5 km. Ideally, accuracy would be improved by calibration of the seismic network using ground‐truth seismic events, such as quarry blasts, but such information is unavailable in this area. Instead, assuming that some earthquakes could be caused by hydraulic‐fracturing in the study area, we statistically associate earthquakes in space and time to fracturing activity. We then use the known locations of this associated activity as proxy ground‐truth to calibrate the seismic network. Our results suggest some earthquakes in west Texas are more likely due to hydraulic‐fracturing than saltwater disposal. Quality measures and spatial patterns of earthquakes relocated using this proxy ground‐truth calibration suggests a real improvement in absolute location accuracy. Key Points: We show that some seismicity in the Delaware Basin, western Texas is likely caused by hydraulic fracturing We use hydraulic‐fracturing as proxy, ground‐truth information to develop station corrections to improve absolute seismic event location Spatial patterns and statistics of west Texas seismicity relocated with these corrections show possible improvement in absolute location accuracy